The U.S. Personal Saving Rate - Ouliaris, Sam (IMF Working Papers; Working Paper, 2018)
This paper develops a time series model for aggregate consumption to predict the U.S. personal saving rate. It then uses the model to test whether there has been a structural break in consumption behavior because of the 2008 financial crisis. Before the crisis, the personal saving rate was trending downwards. However, in 2008 there was a significant rise in the saving rate that continued until the end of 2012, suggesting a permanent change in household behavior. To assess this issue formally, the unknown parameters of the model are estimated using data for 1961Q1-2007Q4, a period which precedes the crisis. The model is then used to predict the saving rate from 2008Q1 onwards and to assess whether the rise in the saving rate after 2008 was due to sizable, but transitory, income/wealth shocks or to changes in the underlying elasticities between saving and its determinants (hence structural). The statistical evidence suggests there was no structural break in the household saving behavior, implying that the rise in the saving rate during 2008-2012 was caused by the negative shocks to income, employment and wealth. This result explains why the saving rate resumed its decline in 2013, as real disposable income, employment and net worth recovered. Assuming that the real growth in these determinants remains strong, the estimated model predicts continued negative pressures on the current account deficit and further external imbalances attributable to the U.S. household sector.